Complete interaction of cellular 56,000- and 32,000-Mr proteins with simian virus 40 small-t antigen in productively infected cells. - Rundell, K (1987)
Two cellular proteins are found to be complexed with simian virus 40 small-t antigen in cellular extracts. The complex is a relatively unstable but dynamic one which can dissociate and reform in extracts. In extracts of permissive monkey kidney cells, the small-t antigen appeared to be present in excess, whereas the cellular proteins were nearly entirely committed to the complex in permissive monkey kidney cells.